Emotionally Naked A Teacher's Guide to Preventing Suicide and Recognizing Students at Risk - Rogers, Anne Moss; Rogers, Anne Moss; O'brien, Kimberly H. Mcmanama (Jossey-Bass, 2021)
Discover effective strategies to help prevent youth suicide In Emotionally Naked: A Teacher's Guide to Preventing Suicide and Recognizing Students at Risk, trainer, speaker, and suicide loss survivor Anne Moss Rogers, and clinical social worker and researcher, Kimberly O'Brien, PhD, LICSW, empower middle and high school educators with the knowledge and skills to leverage their relationships with students to reduce this threat to life. The purpose of this book is not to turn teachers into therapists but given the pervasive public health problem of suicide in our youth, it's a critical conversation that all educators need to feel comfortable having. Educators will learn evidence-based concepts of suicide prevention, plus lesser known innovative strategies and small culture shifts for the classroom to facilitate connection and healthy coping strategies, the foundation of suicide prevention. Included is commentary from teachers, school psychologists, experts in youth suicidology, leaders from mental health nonprofits, program directors, and tudents. In addition, readers will find practical tips, and sample scripts, with innovative activities that can be incorporated into teaching curricula. You'll learn about: The teacher's role in suicide prevention, intervention, postvention, collaboration The different and often cryptic ways students indicate suicidality What to do/say when a student tells you they are thinking of suicide Small shifts that can create a suicide-prevention classroom/school environment How to address a class of grieving students and the empty desk syndrome Link to a download of resources, worksheets, activities, scripts, quizzes, and more Who is it for: Middle/high school teachers and educators, school counselors, nurses, psychologists, coaches, and administrators, as well as parents who wish to better understand the complex subject of youth suicide.